The Influence of Communication, Occupational Health and Safety, and Compensation on the Work Ethic of Healthcare Workers (A Case Study of Healthcare Workers at Dustira Hospital, Cimahi) - Wulansari, Dita Novia; Muhardi, Muhardi; Adwiyah, Rabiatul (Yayasan Gema Bina Nusantara, 2025)
Communication, work safety and health, and compensation are important fields that must be routinely reviewed by the organization that related to services, such as hospital. This is caused by the amount of effect that may occur if there is a problem or conflict on the fields mentioned. One of the things that can be affected is work ethic. The aim of this research was to determine the communication, work safety and health, compensation, and work ethic at Dustira Hospital. The other purpose was to find out how communication, work safety and health, and compensation partially and simultaneously affect the work ethic. This research was an analytical observational study with a cross-sectional study design. Data was taken through questionnaire. The respondents were health practitioners who work at emergency room, hospital clinics, and inpatient care facility, by a population of 115 respondents. Data was analyzed by multiple linear regression. Results showed that the health practitioners at Dustira Hospital has a good communication, work safety and health, and compensation. There was also an influence of compensation and work safety and health on work ethic, partially with the effect of medium criteria variable and simultaneously with the effect of strong criteria variable.